ANALISA PROSES DAN FINANSIAL PERMEN DENGAN APLIKASI SUSU KAMBING DAN SUSU SAPI AFKIR - Wahyu Mushollaeni; Endang Rusdiana (BUANA SAINS, 2009)
Cow and goat’s milk are animal husbandry’s products which are very easily damaged. Quality and price declines with along storage. Therefore, its necessary to find a technology to increase the selling value of cow and goat's milk that is not fresh or otherwise disposed of, but are still suitable for consumption. This was an experimental study using paired t test to compare the quality of unfresh cow's milk and goat’s milk candy. The aimed of this research were to analyze the financial feasibility of the process and the use of unfresh goat milk and cow's milk in a candy rejects. The best treatment was the used of goats milk, with fat content, protein, vitamin C and water content were 14,9%; 12,7%; 0,22% and 14,57%. Financial aspects of this best result were Payback Period 4,267 years; Net BC ratio 1,705; BC ratio 1,347; NPV (18%) Rp. 17.645.615,90; BEP 3.912,40 packs or Rp 24.691.930,99 or 20,4%; and also IRR 28,4%